Body modification technologies and transvestite and trans people in Argentina: A quantitative study on inequalities in use and access - Anahí Farji Neer; María Alejandra Dellacasa; Sebastián Ezequiel Sustas; Melina Antoniucci; Cecilia Rustoyburu; Clara Inés Noceti; Natacha Mateo; Alejandra Rosario Roca (Salud Colectiva)
Collective health has provided valuable analytical perspectives for understanding the social determinants of health and how dynamics of inequality, inequity, and injustice contribute to suffering, disease, morbidity, and mortality. From this perspective, this study identifies and analyzes the ways in which transvestite and trans people in Argentina appropriate and use different hormones and body modification interventions, aiming to highlight the vulnerabilities associated with these practices, both those performed outside the healthcare system and those carried out with professional support in an institution. A quantitative methodological strategy was adopted, with a descriptive, observational, and cross-sectional design. In 2023, a nationwide survey was conducted using a questionnaire targeting transvestite and trans people aged 16 and older (n=1,196). The analyzed data reveal vulnerability processes that do not extend uniformly across the entire population and are linked to health inequalities.